PENGARUH GREEN ACCOUNTING, KINERJA KEUANGAN DAN TAX AVOIDANCE TERHADAP NILAI PERUSAHAAN - Natasya Nur’alifiah Octaviani; desi jelanti (Publika Citra Media, 2026)
This study aims to analyze the influence of green accounting, financial performance, and tax avoidance on company value in the consumer non-cyclicals sector listed on the Indonesia Stock Exchange (IDX) in 2019–2023. The study uses an associative quantitative method with secondary data in the form of financial reports and analyzed using panel data regression through E-Views 12. The sample was selected using a purposive sampling method of 45 companies. The results show that green accounting has no effect on company value, financial performance proxied by ROA has an effect on company value, while financial performance proxied by ROE has no effect on company value and tax avoidance has an effect on company value.